Desorption/ionization-MS methods for drug quantification in biological matrices and their validation following regulatory guidance - Fresnais, Margaux; Burhenne, Jürgen; Haefeli, Walter E.; Longuespée, Rémi (Analytical chemistry, 2021)
Desorption/ionization (DI) methods play an important role among the panel of mass spectrometric (MS) approaches for the rapid and sensitive quantification of drugs from the surface of solid samples. The possibility to implement these approaches for pharmacokinetic/pharmacodynamic investigations in early phase clinical trials depends on the ability to validate quantification assays according to regulatory guidelines (e.g., US Food and Drug Administration and European Medicines Agency) for bioanalytical method validation. However, these guidelines were designed for the validation of liquid chromatography-MS (LC-MS) methods and ligand binding assays. To apply the validation parameters to DI-MS methods (also referred here as on-surface MS) for drug quantification, it is important to consider the particularities of DI approaches compared to LC-MS methods. In this Perspective, we summarize the various applications of on-surface MS methods for drug quantification with their advantages over other MS methods, and provide our point of view regarding future proper method development and validation.